Assessing Dynamics of Control Through Iranian Technology Transfer to Yemen's Houthis. Issue 4 (29th July 2022) - Thompson, Henry; Watling, Jack
Abstract : This article examines the scale and significance of Iranian technology transfer to Ansar Allah in Yemen in underpinning the Houthi way of war. Henry Thompson and Jack Watling consider how Iran balances the transfer of manufacturing capabilities versus the provision of complete systems to exercise influence over the Houthis' strikes on their adversaries. The article argues that the provision of key components gives Iran intimate access to Houthi planning, and therefore extensive indirect influence over how the Houthis fight. This structural dependence enables Iran to exercise command decisions without the need to intrusively exercise control. ◼